Predatory insects – regulators of number of harmful arthropods and their ecological features in the the south-east of Kazakhstan (Eurasian Journal of Ecology, 2016)
In this article, the Biological and ecological features of predatory arthropods are given in this article as regulators of number of insects of wreckers in nature. On purpose use on biocontrol of insects of wreckers.
Keywords: predatory arthropods; insect’s wreckers; ecological features; regulators of number of insects; south – east of Kazakhstan.